A new perspective on ancient Mitis group streptococcal genetics. Issue 2 (28th February 2022) - Belman, Sophie; Chaguza, Chrispin; Kumar, Narender; Lo, Stephanie; Bentley, Stephen D.
Abstract : Mitis group Streptococcus are human obligate bacteria residing in the nasopharynx and oral cavity. They comprise both commensal and pathogenic species with the most well-known being Streptococcus pneumoniae – a leading cause of meningitis and pneumonia. A primary difference between the commensal and pathogenic species is the presence of the polysaccharide capsule – a major virulence factor in S. pneumoniae, also present in other commensal species. Our current understanding of the evolutionary divergence of the pathogenic and commensal species has been inferred from extant strains. Ancient genomes can further elucidate streptococcal evolutionary history. We extracted streptococcal genome reads from a 5700-year-old ancient metagenome and worked towards characterizing them. Due to excessive within- and between-species recombination common among streptococci we were unable to parse individual species. Further, the composite reads of the ancient metagenome do not fit within the diversity of any specific extant species. Using a capsular gene database and AT-content analysis we determined that this ancient metagenome is missing polysaccharide synthesis genes integral to streptococcal capsule formation. The presence of multiple zinc metalloproteases suggests that adaptation to host IgA1 had begun and the presence of other virulence factors further implies development of close host–microbe interactions, though the absence of a capsule suggests an inability to cause invasive disease. The presence of specific virulence factors such as pneumolysin implies stable maintenance of such genes through streptococcal evolution that may strengthen their value as anti-pneumococcal vaccine antigens, while maintaining awareness of their potential presence in commensal species. Following from Jensen et al. 's initial analysis we provide historical context for this long time human nasopharyngeal resident, the Mitis group Streptococcus .